The Impact of SPAC Mergers on Financial Performance and Growth: Evidence from the Italian Market - Domenico Piatti (European Scientific Journal, ESJ, 2024)
This study examines the impact of SPAC mergers on the financial performance of Italian firms, focusing on profitability (ROE, ROI), sales growth, and workforce expansion. A sample of business combinations completed between 2015 and 2019 is analyzed using firm-level data from 2013 to 2022. A Propensity Score Matching (PSM) and Difference-in-Differences (DiD) methodology is applied to control for selection bias and assess the causal effects of SPAC mergers. Additionally, non-linear quantile regression is used to capture the heterogeneous effects across firms. The results show a significant decline in profitability post-merger, particularly in ROE and ROI, likely due to integration challenges. While sales growth improves overall, the non-linear analysis reveals that only a subset of firms experiences significant revenue growth. The findings highlight the importance of strategic planning and regulatory oversight in optimizing SPAC mergers, addressing a critical gap in the Italian market where research is limited. This analysis provides valuable insights for managers and policymakers navigating the evolving SPAC landscape in Italy.